Pharmacological actions of Opuntia ficus indica: A Review - Manpreet Kaur, Amandeep Kaur, Ramica Sharma (Journal of Applied Pharmaceutical Science)
Cactus (Opuntia ficus-indica) belongs to the family Cactaceae. Family Cactaceae is reported to contain about 130 genera and nearly 1500 species. This plant is native of Mexico and it is widely distributed in Mexico and in all American hemispheres as well as in Africa and in the Mediterranean basin. It has been used in traditional folk medicine because of its role in treating a number of diseases and conditions, including anti-inflammatory effects hypoglycemic effects inhibition of stomach ulceration, neuroprotective effects Through antioxidant actions and also used for treating diabetes, burns, bronchial, asthma and indigestion in many countries over the world. It is also used in Pharma industry as a pharmaceutical agent. The fruit, as well as cactus stem are used to prepare value-added products, such as jam, squash, wine, pickle, body lotions, shampoo, creams, etc. It also has several medicinal and industrial uses. Its seeds can be used as flavoring agents. Due to the remarkable biological activity of Opuntia and its constituents, it will be appropriate to develop them as a medicine.
Keywords: Opuntia ficus indica,Cactus,flavonoid,pharmacological action.